2018
DOI: 10.17159/2078-5151/2018/v56n4a2336
|View full text |Cite
|
Sign up to set email alerts
|

Voice prosthesis related expanding tracheoesophageal puncture repair: microsurgical reconstruction to pedicled pectoralis major muscle flap

Abstract: Case Series Over a 3-year period, 42 patients underwent radical laryngectomy and bilateral neck levels 4 and 5 nodal dissection with the insertion of a Provox® VRD post radiotherapy. Three patients developed an expanding TEP that was recalcitrant to non-surgical conservative management, two of whom failed free flap surgery. Their final repair was a PMMF as described below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…1 ). 9 10 11 13 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 Using the OCEBM, 33 studies had a level of evidence of 4. No discrepancies during quality assessment occurred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). 9 10 11 13 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 Using the OCEBM, 33 studies had a level of evidence of 4. No discrepancies during quality assessment occurred.…”
Section: Resultsmentioning
confidence: 99%
“…A butterfly cartilage autograft to enforce TEP closure is an acceptable alternative that can be performed under local anesthesia and is associated with low morbidity. 42 This technique is elaborately described by Yenigun et al who reported that enteral feeding was resumed in a short span of time. 42 Likewise, FL autograft is also described as an excellent method for three-layered fistula closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation